10 Long-term outcomes of adults with williams syndrome in an adult congenital heart disease centre. (28th April 2017) - Ooues, G; Thorne, S; Bowater, S; Clift, P; Hudsmith, L
Abstract : Background: Williams syndrome, is a congenital, multisystem disorder, involving the cardiovascular, connective tissue and central nervous systems. We sought to determine long-term outcomes of these patients in our Adult Congenital Heart Disease Service. Methods: A retrospective review of case notes of patients with Williams syndrome was performed, reviewing clinic letters, operation details and cardiac imaging. Results: We identified 37 adults with Williams syndrome (62% male) with mean age 30±9.6 years (range, 19 to 56 years). 6 patients (16%) were discharged after their first review as no cardiovascular abnormalities were identified. One patient was lost to follow-up. Mean follow-up of the rest was 7.9±4.6 years (range, 6 months to 15 years). Most common cardiovascular manifestations included systemic arterial hypertension (40%, n=12), supravalvar aortic stenosis (57%, n=17; repaired (n=10)), pulmonary artery stenosis (30%, n=9; operated (n=5)) and aortic coarctation (20%, n=6; repaired (n=4)). At last clinic review, 10 patients (33%) were NYHA II (n=9) or NYHA III (n=1). 12 patients (40%) were hypertensive (BP >140 systolic), despite being on antihypertensive treatment (n=8). All patients were in sinus rhythm and no arrhythmias were identified. 9 patients (30%) had prolonged QTc (>440 ms in men or >460 ms in women). The majority (97%, n=29) had good left ventricular function (mean EF 63%±4.6%), and only one patient had mild impairment (EF 50%). No significant post-operative gradients were measured. Conclusion: Long-term follow-up of patients with Williams syndrome and significant cardiovascular disease is essential with particular care to blood pressure control.